2014
DOI: 10.1063/1.4904705
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational effects on valence electron momentum distributions of CH2F2

Abstract: We report an electron momentum spectroscopy study of vibrational effects on the electron momentum distributions for the outer valence orbitals of difluoromethane (CH2F2). The symmetric noncoplanar (e,2e) experiment has been performed at an incident electron energy of 1.2 keV. Furthermore, a theoretical calculation of the electron momentum distributions of the CH2F2 molecule has been carried out with vibrational effects being involved. It is shown from comparisons between experiment and theory that it is essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 57 publications
(83 reference statements)
1
28
1
Order By: Relevance
“…Comparisons between experiment and theory has shown that taking into account vibrational effects lead to appreciable enhancement of the low p component of the 7t 2 , {2t 1 +3e} and {5t 2 +5a 1 } momentum profiles and considerably improve the agreement with experiment. Further analysis based on the HAQM approach has revealed the significant role of vibrational modes associated with the CH bonds, in line with previous results on molecules with several CH bonds 30,[34][35][36]38 in their contribution to the change of momentum profiles.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Comparisons between experiment and theory has shown that taking into account vibrational effects lead to appreciable enhancement of the low p component of the 7t 2 , {2t 1 +3e} and {5t 2 +5a 1 } momentum profiles and considerably improve the agreement with experiment. Further analysis based on the HAQM approach has revealed the significant role of vibrational modes associated with the CH bonds, in line with previous results on molecules with several CH bonds 30,[34][35][36]38 in their contribution to the change of momentum profiles.…”
Section: Discussionsupporting
confidence: 88%
“…From such an analysis, we have found that vibrational effects for the 7t 2 , {2t 1 +3e}, and {5t 2 +5a 1 } orbitals cannot be ascribed to only a few specific normal modes; the contributions are distributed over a number of modes due to the large degrees of vibrations freedom of the adamantane molecule. This is in contrast with findings made recently for smaller molecules, such as C 2 H 4 30 and CH 2 F 2 , 34 where only a few normal modes play dominant roles. To facilitate the interpretation of results, the classification of vibrational modes proposed by Jensen 50 has then been adopted, where each of modes is assigned to one of nine types of motions: CC stretch, CH stretch, CCC bend, CCC wag, CH wag, CH 2 scissors, CH 2 twist, CH 2 wag, and CH 2 rock motions.…”
Section: Contributions From Individual Vibrational Modescontrasting
confidence: 94%
See 3 more Smart Citations